Application of Artificial Intelligence in Cardiopulmonary Resuscitation - LIU Shuai; ZHU Huadong (Xiehe Yixue Zazhi, 2023)
With the development of artificial intelligence, computer hardware and big data, more and more artificial intelligent devices and algorithm are springing up. Based on the analysis of these data, great achievements has been made by artificial intelligent devices to predict the risk of the cardiac arrest, identify early period of cardiac arrest, instruct the process to improve the quality of cardiopulmonary resuscitation and resuscitation prediction. Meanwhile these tools not only provide new insight for clinical research, but play significant roles in clinical decision making and medical resources distribution. This paper focuses on the application of artificial intelligence in cardiopulmonary resuscitation, in order to provide reference for clinical practice.